Temanggung Local Coffee Marketing Potential Through Marketplace: Tokopedia, Bukalapak, Shopee, Which Is The Best? - Edhita Praja, Chrisna Bagus; Setiyo, Muji; Lutfiyati, Heni (Muhammadiyah University Press, 2018)
This paper compares the three largest marketplaces in Indonesia as a marketing platform for temanggung coffee products. The three marketplaces are tokopedia, bukalapak, and shopee. PPPUD Team of Universitas Muhammadiyah Magelang accompanied two partners, namely Palatiga Coffee SMEs and Garuda Coffee SMEs in product marketing through the marketplace. Tokopedia is one of the marketplaces that have a high user rating and has the complete features of the two other marketplaces. Also, Tokopedia also supports Indonesian coffee by providing a special page of Hot List Kopi Indonesia. PPPUD team of Universitas Muhammadiyah Magelang is currently developing marketing through Tokopedia and does not rule out the possibility to expand the market by opening a shop in Bukalapak and Shopee